Epicocconone staining: A powerful loading control for Western blots. Issue 2 (February 2014) - Moritz, Christian P.; Marz, Sabrina X.; Reiss, Ralph; Schulenborg, Thomas; Friauf, Eckhard
<x xml:space="preserve">Abstract</x> Western blot analysis is routinely employed for quantifying differences in protein levels between samples. To control equal loading and to arithmetically compensate loading differences, immunodetection of housekeeping proteins is commonly used. Due to potential biases, this approach has been criticized. Here, we evaluate epicocconone‐based total protein staining (E‐ToPS) as an alternative. We compared it with two other total protein stainings (Coomassie and Sypro Ruby) and with immunodetection of housekeeping proteins (β‐tubulin and glyceraldehyde 3‐phosphate dehydrogenase). Evaluation comprised both the natural and the synthetic epicocconone compound. Both compounds produced highly congruent results and showed more sensitive (≤ 1 μg) and less variable staining properties than the other variants. The high sensitivity of E‐ToPS, covering minute protein amounts, makes it a powerful loading control, especially for precious samples. Regarding biological and technical variances, E‐ToPS outperformed immunostaining against β‐tubulin and glyceraldehyde 3‐phosphate dehydrogenase. Furthermore, E‐ToPS had no impact on subsequent immunodetection, allowing for an early control of proper loading prior to immunodetection. In contrast to earlier studies, we found logarithmic staining properties for E‐ToPS, which should be considered when using it for arithmetic normalization. In conclusion, we demonstrate the superior power of E‐ToPS as a loading control for Western blots.